Desempenho produtivo de bovinos cruzados em sistemas de Integração Lavoura-Pecuária - Patrícia Monteiro Costa (2017)
Two studies were conducted with beef cattle in integrated systems. The first study was aimed to evaluate the performance of crossbred steers in a crop-livestock integration system during the post-weaning stage and finished in the feedlot, fed high or exclusively concentrated diets. Weaned calves of two breed groups ½ Angus × ½ Nellore and ½ Charolais × ¼ × Angus ¼ Nellore were allotted in a randomized complete design. During the dry season there were no differences in animal performance, but in the rainy season, the ½ Angus × ½ Nellore animals showed higher performance than ½ Charolais × ¼ × Angus ¼ Nellore, with average daily gain of 0.748kg and 0.490kg respectively. The productivity in growing period was 926 kg ha-1 of body weight in 11 months, in ILP system. Subsequently, the animals were confined and fed high-concentrate or concentrate-only diets, the experimental design wasrandomizedcomplete,set in a 2 × 2 factorial arrangement (type of cross × type of diet). In confinement, independent of assessed diet, ½ Charolais × ¼ × Angus ¼ Nellore animals showed lower carcass average daily gain, carcass yield and slaughter weight than the ½ Angus × ½ Nellore animals. The high production of kilograms in the system demonstrates that, associated with the use of crossbreeding during post-weaning and finishing stages, this strategy can be indicated for the new demand of a sustainable livestock activity.The second study was aimed at evaluating the effects of integrating agriculture with livestock using different beef cattle genetic groups in two consecutive years. The performance of animals of the AN and CAN genetic groups was evaluated during the post-weaning stage on pasture in a ILP system and during the finishing stage in the feedlot, where they were fed high-concentrate diets originating from the ILP system. In the post-weaning stage, animals were reared on a ILP system, receiving supplementation (protein supplement in the dry season and mineral supplement in the rainy season of the first year; protein supplement in the rainy and dry seasons of the second year). We evaluated animal performance and the impacts on the productivity of the cattle herd and estimated enteric methane emission by the cattle (IPCC - 2006). The randomized block experimental design was adopted. Angus animals showed an ADG of 0.711 kg during the post-weaning stage, which was higher than that of CAN cattle, whose ADG was 0.545 kg; however, no difference in animal performance was observed in the feedlot period. The intercropped ILP systems provided an average yield of 38.41@ ha yr1. Methane emission estimates per kilogram of live weight produced were lower than those found in the traditional, extensive beef cattle rearing systems. The increased yield of this system is a reflection of strategies like ILP, strategic dietary supplementation, and proper pasture management and feedlot. Cattle farming in a ILP system is a sustainable activity, given its greater yield without the need for association of new areas for animal production, in addition to the consequent possibility of lessening deforestation, thereby reducing negative environmental impacts.